2019
DOI: 10.5336/cardiosci.2018-62841
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin on Metabolic Syndrome Components

Abstract: Ö ÖZ ZE ET T Kurkumin, zerdeçal olarak bilinen Curcuma longa isimli bitkinin köklerinden elde edilmektedir. Kurkuminin glikoliz aktivasyonu, hepatik glukoneogenezin inhibisyonu ve lipit metabolizmasının azaltılması yoluyla glukoz homeostazına aracılık etmektedir. Nükleer faktör-kappa B inhibitörü olan kurkumin insülin direncinin hafifletilmesinde yardımcıdır; peroksizom proliferatörü aktive reseptör gamayı aktive ederek hipoglisemik etkiler göstermekte ve böylece kan glukoz seviyelerindeki artışları baskılayab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…[9] The prevalence of CHD was found to be 8 per 1000 in studies conducted in Turkey, which is similar to the rates reported in the Western countries. [4][5][6] In our retrospective study based on selected subjects, 27.7% of the subjects were diagnosed with CHD by echocardiography. This rate was higher in our study compared with that present the literature is because our study was not a populationbased study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] The prevalence of CHD was found to be 8 per 1000 in studies conducted in Turkey, which is similar to the rates reported in the Western countries. [4][5][6] In our retrospective study based on selected subjects, 27.7% of the subjects were diagnosed with CHD by echocardiography. This rate was higher in our study compared with that present the literature is because our study was not a populationbased study.…”
Section: Discussionmentioning
confidence: 99%
“…[3] A limited number of studies exist on the distribution of CHD in Turkey. [4][5][6] Our study aimed to investigate the prevalence and distribution of CHD and comorbidities in children who underwent transthoracic echocardiography between January 2013 and December 2015 at the pediatric cardiology clinic.…”
Section: Introductionmentioning
confidence: 99%